Kedudukan Hak Menguasai Negara Atas Tanah - Daeng Kunu, Andi Bustamin (FIAT JUSTISIA)
The existence of mastering rights of the state for land is the constitutional base for state to arranging the exploitation of land in Indonesia for the maximum of people prosperity. The Competention as expressed in Section 33 sentence ( 3) UUD 45 and get furthermore coherent in Section 2 sentence ( 1) UUPA, so that state in conducting arrangement have to pursuant to law which populis for the maximum of people prosperity. State as a personification of all people was given the mastering rights. Its target is to give the service in arranging exploiting of the natural resource of the nation to reach the target of land exploiting to give the competent life for as much as possible people.